(452) the Development of U.A.R's Foreign Exchange Policy تطور سياسة الصرف الأجنبي لجمهورية أرمينيا - ابراهيم حسن العيسوي (معهد التخطيط القومي, 2026)
This study examines the development of foreign exchange policy in the United Arab Republic (U.A.R.) during the period 1939–1963, with particular emphasis on the transformation of its role under the emergence of comprehensive national planning in the early 1960s. The study is based on the premise that foreign exchange policy should not be viewed merely as an instrument for regulating international transactions or correcting short-term balance-of-payments disequilibria; rather, it should be integrated into a broader economic planning framework. The study begins by presenting the theoretical foundations of foreign exchange control, including its concept, objectives, and alternative forms. Particular attention is given to quantitative restrictions, cost-based restrictions, multiple exchange-rate systems, and trade and payments agreements. The study also compares exchange-control measures with alternative policy instruments such as tariffs, quotas, and currency depreciation mechanisms .Furthermore, the document traces the historical evolution of foreign exchange policy in Egypt beginning in 1939. It reviews the country's relationship with the Sterling Area, the introduction of exchange controls during World War II, and the subsequent adjustments associated with economic and political changes. The study examines several policy mechanisms, including export pound procedures, import entitlement systems, barter arrangements, and both multiple and unified exchange-rate systems. Special emphasis is placed on the relationship between foreign exchange policy and national planning. The study discusses the concept and functions of the foreign exchange budget, the principles of its preparation, and its integration into national development plans. Foreign exchange policy is therefore presented as an important planning instrument for allocating scarce resources according to development priorities. The study concludes that the evolution of exchange-control systems reflects the changing role of the state in economic management and that the effectiveness of foreign exchange policy depends largely on its integration with broader planning objectives and development strategies.